Undercover investigations in the workplace - Ferraro, Eugene F. (Butterworth-Heinenemann, 2000)
This book defines and explores the process of undercover investigations as well as delving into the legal aspects of undercover and the role of an effective litigation avoidance strategy. Undercover Investigations makes a rational and authoritative plea for legitimacy of undercover in the workplace.